Transcultural writers and novels in the age of global mobility - Dagnino, Arianna, 1963- (Comparative cultural studies., 2015)
In Transcultural Writers and Novels in the Age of Global Mobility, Arianna Dagnino analyzes a new type of literature emerging from artists increased movement and cultural flows spawned by globalization. This ""transcultural"" literature is produced by authors who write across cultural and national boundaries and who transcend in their lives and creative production the borders of a single culture. Dagninos book contains a creative rendition of interviews conducted with five internationally renowned writersInez Baranay, Brian Castro, Alberto Manguel, Tim Parks, and Ilija Trojanowand a critical e.